2006
DOI: 10.1002/app.23074
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and property evaluations of photocrosslinkable chitosan derivative and its photocopolymerization with poly(ethylene glycol)

Abstract: Photocrosslinkable polymers are clean and convenient materials for the biomedical uses. Chitosan, which owns excellent biocompatible and antimicrobial properties, is one of the choices while it is introduced with photosensitive functional groups. In this study, chitosan was N-phthaloylated to react with acryloyl chloride in the organic solvent homogeneously and the result has been verified by the solubility test. Fourier transformed infrared spectrometry and nuclear magnetic resonance spectrometer analysis ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Because of its chemical structure, chitosan shows high biocompatibility leading to its being extensively applied in biomedical areas, for such uses as surgical sutures, dental implants, artificial skin, and so forth 9. In recent research, chitosan has been widely used as a scaffolding material for tissue engineering 15, 21–27. Many studies indicate that chitosan is suitable for orthopedic applications 1, 6, 11–14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its chemical structure, chitosan shows high biocompatibility leading to its being extensively applied in biomedical areas, for such uses as surgical sutures, dental implants, artificial skin, and so forth 9. In recent research, chitosan has been widely used as a scaffolding material for tissue engineering 15, 21–27. Many studies indicate that chitosan is suitable for orthopedic applications 1, 6, 11–14.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that chitosan is a good candidate for orthopedic applications 1, 6, 11–14. In cartilage tissue engineering, chitosan was shown to promote chondrocyte attachment and proliferation and maintain chondrogenic phenotype, which may be due to its structural similarity to various glycosaminoglycans (GAGs) found in articular cartilage 8, 11, 15, 16. Chitosan has also been extensively used in bone tissue engineering as it has been shown to facilitate growth and biomineralization by osteoblasts 14.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the most commonly used method to prepare photocrosslinkable CS is by grafting methacryloyl groups to CS molecular chain. For instance, Tsai et al prepared acryloyl CS (4 in Fig. ) by the reaction between N ‐phthaloylated CS and acryloyl chloride in the organic solvent homogeneously.…”
Section: Synthesis Of Photoactive Cs Macromersmentioning
confidence: 99%
“…Ma et al [8] prepared photopolymerizable chitosan derivative by chitosan and stearyl chloride in mixture of triethylamine and acetone. Moreover, Tsai et al [9] introduced acryloyl chloride into N-phthaloyl chitosan to obtain photosensitive chitosan derivative with unsaturated bond.…”
Section: Introductionmentioning
confidence: 99%